After the Rain - Osborne, Mary Pope (New York : Scholastic, 2002)
In her diary, a ten-year-old girl writes about her family's experiences living in Washington, D.C., in 1864-65, during which time the Civil War comes to an end and President Lincoln is assassinated. Includes historical notes.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Fiction; Diaries -- Fiction; Washington (D.C.) -- Fiction -- History -- Civil War, 1861-1865; Washington (D.C.) -- Fiction -- History -- Civil War, 1861-1865; United States -- Fiction -- History -- Civil War, 1861-1865